Stone-like self-leveling paint and preparation process thereof
By preparing a rigid-flexible structured bifunctional diluent, the problems of excessive viscosity and insufficient mechanical properties of epoxy colored sand self-leveling paint were solved, and low-viscosity construction and performance improvement were achieved.
Patent Information
- Application Number
- CN202511281887.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-09
- Publication Date
- 2025-10-10
- Estimated Expiration
- 2045-09-09
AI Technical Summary
The viscosity of epoxy colored sand self-leveling paint is too high, which affects the suspension uniformity and leveling of the colored sand, and the existing diluent affects the mechanical properties.
A rigid-flexible structured bifunctional diluent was prepared by nucleophilic substitution and epoxidation treatment to reduce the viscosity of epoxy resin and enhance the mechanical properties.
It realizes the low-viscosity construction of epoxy colored sand self-leveling paint, improves the leveling and mechanical properties, and enhances water resistance and corrosion resistance.
Smart Images

Figure SMS_11 
Figure SMS_12 
Figure SMS_13
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of epoxy color sand self-leveling paint, in particular to a stone-like self-leveling paint and a preparation process. BACKGROUND
[0002] The epoxy color sand self-leveling paint is not a traditional stone-like paint, but has a stone-like effect. The epoxy color sand self-leveling paint takes epoxy resin as a base material, adds color quartz sand or glass sand as an aggregate, and is constructed by a self-leveling process to form a seamless, high-strength and highly decorative ground coating.
[0003] In order to obtain good leveling property and color sand suspension effect, the overall viscosity of the epoxy resin system should be maintained at 1000-3000 mPa·s. However, the viscosity of the epoxy resin main agent is relatively large, generally above 8000 mPa·s. Therefore, in the epoxy color sand self-leveling paint, the epoxy resin main agent must be modified to reduce the viscosity, so that the epoxy resin system has low viscosity characteristics to ensure uniform suspension of the color sand and meet the construction requirements of the self-leveling process.
[0004] Research shows that the epoxy color sand self-leveling paint is a solvent-free system, and the viscosity of the epoxy resin main agent can be reduced by using an active diluent. The types of the active diluent include monofunctional (specific products are n-butyl glycidyl ether , the dosage range is 5-15%), bifunctional (specific products are 1,4-butanediol diglycidyl ether , the dosage range is 10-20%), and polyfunctional (specific products are trimethylolpropane triglycidyl ether , the dosage range is 5-10%).
[0005] The monofunctional diluent in the above low molecular weight aliphatic epoxy compound reduces the crosslinking density of the cured product, and the bifunctional and polyfunctional diluents dilute the proportion of rigid structures in the cured product, which affects the mechanical properties of the epoxy color sand self-leveling paint film. SUMMARY
[0006] The present application develops a new bifunctional diluent with rigid-flexible structure through molecular design. The rigid structure overcomes the defect of the low molecular weight aliphatic epoxy compound diluting the proportion of rigid structures in the cured product, and the flexible structure reduces the viscosity of the epoxy resin main agent to improve the leveling property during construction, and also has a toughening effect.
[0007] A stone-like self-leveling paint comprises the following raw materials in parts by weight: 45-55 parts of bisphenol A glycidyl ether type epoxy resin; 5-15 parts of rigid-flexible structured bifunctional diluent; 10-15 parts of filler; 5-15 parts aggregate; 15-20 parts of curing agent; 0.1-0.5 parts of curing accelerator; The bifunctional rigid-flexible structured diluent is prepared by firstly reacting a 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane or a terminal chloromethyl hexasiloxane monomer providing a flexible structure with a 3-cyclohexene-1-methanol providing a rigid structure, and then epoxidizing the cyclohexene group. Among them, the bifunctional rigid-flexible structured diluent is bifunctional rigid-flexible structured diluent X-Ⅰ or bifunctional rigid-flexible structured diluent X-Ⅱ.
[0008] Preferably, the filler is one or a combination of kaolin, talc, calcium carbonate, and barium sulfate.
[0009] Preferably, the aggregate is colored quartz sand or glass sand.
[0010] A preparation process of a stone-like self-leveling paint comprises the following steps: Step 1: According to the formula of the stone-like self-leveling paint, bisphenol A glycidyl ether epoxy resin and a bifunctional rigid-flexible structural diluent are first mixed, and then fillers and aggregates are added and stirred evenly to obtain an epoxy resin composition; Step 2: According to the formula of the imitation stone self-leveling paint, the curing agent and the curing accelerator are mixed uniformly to obtain a curing agent composition; Step 3: adding the curing agent composition to the epoxy resin composition and stirring evenly to obtain the stone-like self-leveling paint.
[0011] Preferably, the preparation method of the bifunctional rigid-flexible structured diluent X-I is: Under the action of a phase transfer catalyst, the chlorine functional group of 1 molar equivalent of 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane reacts with the hydroxyl functional group of 2.01-2.09 molar equivalents of 3-cyclohexene-1-methanol to produce a terminal cyclohexenyl disiloxane monomer; Under the oxidizing action of organic peroxyacid, the cyclohexene functional group in the terminal cyclohexenyl disiloxane monomer undergoes epoxidation reaction to generate a bifunctional rigid-flexible structured diluent X-Ⅰ.
[0012] Preferably, the preparation method of the bifunctional rigid-flexible structured diluent X-II is: Under the action of a phase transfer catalyst, the chlorine functional group of 1 molar equivalent of 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane reacts with the hydroxyl functional group of 2.01-2.09 molar equivalents of 3-butene-1-ol to produce a terminal alkenyl disiloxane monomer; Based on the silanol condensation reaction mechanism, a hydrogen-containing chloromethylsiloxane monomer is generated by a condensation reaction between the hydrolysis product of 1 molar equivalent of chloromethylethoxydimethylsilane and the hydrolysis product of 1.01-1.09 molar equivalents of dimethylethoxysilane; The terminal chloromethyl hexasiloxane monomer is generated by an addition reaction of the alkenyl functional group of 1 molar equivalent of the terminal alkenyl disiloxane monomer with the Si-H functional group of 2.01-2.09 molar equivalents of the hydrogen-containing chloromethylsiloxane monomer; Under the action of a phase transfer catalyst, a chlorine functional group of 1 molar equivalent of a terminal chloromethyl hexasiloxane monomer and a hydroxyl functional group of 2.01-2.09 molar equivalents of 3-cyclohexene-1-methanol undergo a nucleophilic substitution reaction to generate a terminal cyclohexenyl hexasiloxane monomer; Under the oxidizing action of organic peroxyacid, the cyclohexene functional group of the terminal cyclohexenyl hexasiloxane monomer undergoes epoxidation reaction to generate a bifunctional rigid-flexible structured diluent X-Ⅱ.
[0013] Preferably, the phase transfer catalyst is one of tetrabutylammonium bromide, tetrabutylammonium hydrogen sulfate, and benzyltriethylammonium chloride.
[0014] Preferably, the organic peroxyacid is one of peracetic acid, perbenzoic acid, and m-chloroperbenzoic acid. Beneficial effects
[0015] The present invention uses a terminal chloromethylsiloxane monomer (1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane or a terminal chloromethylhexasiloxane monomer) that provides a flexible structure to undergo a nucleophilic substitution reaction with 3-cyclohexene-1-methanol that provides a rigid structure. The cyclohexene group is then epoxidized to obtain a bifunctional rigid-flexible structured diluent connected by a flexible ether bond. The epoxy resin base material is modified to reduce viscosity by using a bifunctional rigid-flexible structured diluent connected by a flexible ether bond. The epoxy colored sand self-leveling paint (also known as a stone-like self-leveling paint product) obtained in this way meets the technical requirements of self-leveling properties specified in industry standards. Compared with traditional reactive diluents, it has achieved significant improvements in mechanical properties while also enhancing weather resistance (mainly water resistance and corrosion resistance). It is particularly suitable for use in scenarios where wear resistance and corrosion resistance are required on the ground. DETAILED DESCRIPTION
[0016] The present application designs and synthesizes two kinds of bifunctional rigid-flexible structured diluents containing a silicon-oxygen flexible chain, an ether group flexible chain and a six-membered rigid alicyclic group. On the one hand, the structure contains a double epoxy group and a flexible structure, which can reduce the viscosity of the system and improve the fluidity when used in epoxy resin, and will not cause the crosslinking density of the epoxy resin cured product to decrease, and ensure the mechanical properties. On the other hand, the structure contains a low surface energy siloxane structure, which can become part of the crosslinking network structure of the epoxy resin cured product when participating in the curing reaction of the epoxy resin, and significantly enhance the water resistance and corrosion resistance. Thirdly, the rigid alicyclic structure contained in the structure can ensure the proportion of rigid structure in the epoxy resin cured network. A stone-like self-leveling paint is prepared by taking bisphenol A glycidyl ether type epoxy resin as a base material, colored quartz sand as an aggregate, a bifunctional rigid-flexible structured diluent as a dilution component, and adding fillers and curing components. Example one:
[0017] The bifunctional rigid-flexible structured diluent X-I is synthesized, and the synthesis process is as follows: Process one: under the action of a phase transfer catalyst, 1 mole equivalent of 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane chloro functional group reacts with 2.07 mole equivalents of 3-cyclohexen-1-methanol hydroxyl functional group to generate a cyclohexenyl-terminated disiloxane monomer, and the chemical structural formula is: ; Among them, the phase transfer catalyst can be selected from one of tetrabutylammonium bromide, tetrabutylammonium hydrogen sulfate, benzyl triethyl ammonium chloride; tetrabutylammonium hydrogen sulfate is selected in this embodiment; Process two: under the oxidation of an organic peroxy acid, the cyclohexene functional group in the cyclohexenyl-terminated disiloxane monomer undergoes epoxidation to generate a bifunctional rigid-flexible structured diluent X-I, and the chemical structural formula is: ; Among them, the organic peroxy acid can be selected from one of peroxoacetic acid, peroxobenzoic acid, m-chloroperbenzoic acid; m-chloroperbenzoic acid is selected in this embodiment; The specific experimental steps for preparing the bifunctional rigid-flexible structured diluent X-I are as follows: 2.3 g of 3-cyclohexene-1-methanol, 5 mL of sodium hydroxide aqueous solution (concentration 10 wt%) and 20 mL of tetrahydrofuran were added to a three-necked flask and stirred at room temperature for 30 min. Then, 20 mL of tetrahydrofuran solution containing 2.3 g of 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane and 10 mL of tetrabutylammonium hydrogen sulfate solution (prepared from 1.1 g of tetrabutylammonium hydrogen sulfate and 10 mL of tetrahydrofuran) were added to the three-necked flask in sequence. The mixture was heated to 70° C. and stirred under reflux for 4 h. The mixture was cooled to room temperature, evaporated under reduced pressure, washed with ethanol, and dried to obtain a terminal cyclohexenyl disiloxane monomer. 1.9 g of cyclohexenyl-terminated disiloxane monomer and 20 mL of chloroform were added to a three-necked flask and stirred at room temperature until completely dissolved. Then, 20 mL of m-chloroperbenzoic acid solution (prepared from 1.5 g of m-chloroperbenzoic acid and 20 mL of chloroform) was added dropwise to the three-necked flask. The mixture was heated to 55° C. and stirred for 12 h. The mixture was cooled to room temperature and washed with saturated sodium bicarbonate aqueous solution and deionized water in sequence. The solvent was removed by rotary evaporation and dried to obtain a bifunctional rigid-flexible structured diluent X-Ⅰ. The hydrogen spectrum characterization of the bifunctional rigid-flexible structured diluent X-Ⅰ is as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.09 (s, 12H), 1.21 (s, 4H), 1.65-2.09 (m, 14H), 3.40-3.42 (d, 4H), 3.48-3.54 (m, 4H). Example 2:
[0018] The synthesis process of the bifunctional rigid-flexible structured diluent X-II is as follows: Process 1: Under the action of a phase transfer catalyst, the chlorine functional group of 1 molar equivalent of 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane reacts with the hydroxyl functional group of 2.05 molar equivalents of 3-butene-1-ol to form a terminal alkenyl disiloxane monomer with the chemical formula: ; Process 2: Based on the silanol condensation reaction mechanism, a condensation reaction occurs between the hydrolysis product of 1 molar equivalent of chloromethylethoxydimethylsilane and the hydrolysis product of 1.06 molar equivalent of dimethylethoxysilane to generate a hydrogen-containing chloromethylsiloxane monomer, the chemical structure of which is: ; Process 3: The alkenyl functional group of 1 molar equivalent of the terminal alkenyl disiloxane monomer reacts with the Si-H functional group of 2.03 molar equivalents of the hydrogen-containing chloromethylsiloxane monomer to generate a terminal chloromethyl hexasiloxane monomer, the chemical structure of which is: ; Step 4: Under the action of a phase transfer catalyst, a nucleophilic substitution reaction occurs between the chlorine functional group of 1 molar equivalent of the terminal chloromethyl hexasiloxane monomer and the hydroxyl functional group of 2.07 molar equivalents of 3-cyclohexene-1-methanol to generate a terminal cyclohexenyl hexasiloxane monomer, the chemical structure of which is: ; Process 5: Under the oxidative action of an organic peroxyacid, the cyclohexene functional group of the terminal cyclohexenyl hexasiloxane monomer undergoes an epoxidation reaction to generate a bifunctional rigid-flexible structured diluent X-II, whose chemical structure is: ; Among them, the phase transfer catalyst can be selected from one of tetrabutylammonium bromide, tetrabutylammonium hydrogen sulfate, and benzyltriethylammonium chloride; in this embodiment, tetrabutylammonium hydrogen sulfate is selected; The organic peroxy acid can be selected from one of peracetic acid, perbenzoic acid, and meta-chloroperbenzoic acid; meta-chloroperbenzoic acid is selected in this embodiment; The specific experimental steps for preparing the bifunctional rigid-flexible structured diluent X-II are as follows: 4.4 g of 3-butene-1-ol, 10 mL of 10 wt% sodium hydroxide aqueous solution and 30 mL of tetrahydrofuran were added to a three-necked flask and stirred at room temperature for 30 min. Then, 60 mL of 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane solution (prepared from 6.9 g of 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane and 60 mL of tetrahydrofuran) and 10 mL of tetrabutylammonium hydrogen sulfate solution (prepared from 1.1 g of tetrabutylammonium hydrogen sulfate and 10 mL of tetrahydrofuran) were added to the three-necked flask in sequence. The mixture was heated to 70° C. and stirred under reflux for 4 h. The mixture was cooled to room temperature, and the solvent was removed by rotary evaporation. The mixture was washed with ethanol and dried to obtain a terminal alkenyl disiloxane monomer. 6.0 g of chloromethylethoxydimethylsilane, 30 mL of anhydrous tetrahydrofuran, and 20 mL of deionized water were added to a three-necked flask and stirred at room temperature for 30 min. Then, 30 mL of dimethylethoxysilane solution (prepared from 4.1 g of dimethylethoxysilane, 20 mL of anhydrous tetrahydrofuran, and 10 mL of deionized water) and 5.5 mL of glacial acetic acid were added to the three-necked flask in sequence. The mixture was heated to 60° C. and stirred for 10 h. The mixture was cooled to room temperature, the solvent was removed by rotary evaporation, and the mixture was dried to obtain a hydrogen-containing chloromethylsiloxane monomer. Under nitrogen protection, 6.0 g of terminal alkenyl disiloxane monomer and 60 mL of tetrahydrofuran were added to a three-necked flask and stirred at room temperature until completely dissolved. Then, 70 mL of hydrogen-containing chloromethylsiloxane monomer solution (prepared by 7.4 g of hydrogen-containing chloromethylsiloxane monomer and 70 mL of tetrahydrofuran) and 5 drops of Custer catalyst were added to the three-necked flask in sequence. The temperature was raised to 70°C and stirred under reflux for 5 h. The mixture was cooled to room temperature, the solvent was removed by rotary evaporation, and the mixture was dried to obtain terminal chloromethyl hexasiloxane monomer. The hydrogen spectrum characterization of the terminal chloromethyl hexasiloxane monomer is: 1 H NMR (CDCl3, 400MHz) δ: 0.06 (s, 12H), 0.10 (s, 12H), 0.20 (s, 12H), 0.99-1.04 (t, 4H), 1.29 (s, 4 H), 1.71-1.79 (m, 4H), 2.04 (s, 4H), 2.72-2.81 (m, 4H), 3.52-3.55 (t, 4H); 2.3 g of 3-cyclohexene-1-methanol, 5 mL of 10 wt% sodium hydroxide aqueous solution, and 20 mL of tetrahydrofuran were added to a three-necked flask and stirred at room temperature for 30 min. Then, 50 mL of a chloromethyl-terminated hexasiloxane monomer solution (prepared from 6.7 g of chloromethyl-terminated hexasiloxane monomer and 50 mL of tetrahydrofuran) and 15 mL of a tetrabutylammonium hydrogen sulfate solution (prepared from 1.5 g of tetrabutylammonium hydrogen sulfate and 15 mL of tetrahydrofuran) were added to the three-necked flask in sequence. The mixture was heated to 70° C. and stirred under reflux for 5 h. The mixture was cooled to room temperature, and the solvent was removed by rotary evaporation. The mixture was washed with ethanol and dried to obtain a cyclohexenyl-terminated hexasiloxane monomer. 4.1 g of cyclohexenyl-terminated hexasiloxane monomer and 40 mL of chloroform were added to a three-necked flask and stirred at room temperature until completely dissolved. Then, 20 mL of m-chloroperbenzoic acid solution (prepared from 1.8 g of m-chloroperbenzoic acid and 20 mL of chloroform) was added dropwise to the three-necked flask. The mixture was heated to 55°C and stirred for 16 h. The mixture was cooled to room temperature and washed with saturated sodium bicarbonate aqueous solution and deionized water in sequence. The solvent was removed by rotary evaporation and dried to obtain a bifunctional rigid-flexible structured diluent X-II. The hydrogen spectrum characterization of the bifunctional rigid-flexible structured diluent X-Ⅱ is as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.04 (s, 12H), 0.07 (s, 12H), 0.11 (s, 12H), 0.90-0.94 (t, 4H), 1.25 (s, 4H), 1.29 ( s, 4H), 1.67-2.01 (m, 18H), 2.72-2.81 (m, 4H), 3.33-3.34 (d, 4H), 3.49-3.52 (t, 4H), 3.57-3.65 (m, 4H). Example 3:
[0019] A stone-like self-leveling paint is composed of a base material, a diluent, a filler, an aggregate and a curing component. The specific formula is shown in Table 1 below: Table 1 Specific formula of imitation stone self-leveling paint
[0020] Among them, the bifunctional rigid-flexible structured diluent is bifunctional rigid-flexible structured diluent X-Ⅰ or X-Ⅱ. Example 4:
[0021] A preparation process of a stone-like self-leveling paint comprises the following steps: Step 1: According to the formula of the imitation stone self-leveling paint, the formula amount of bisphenol A glycidyl ether type epoxy resin and the bifunctional rigid-flexible structured diluent are mixed, and the mixture is stirred at a speed of 600 r / min for 10 minutes. Then, the formula amount of talc powder, calcium carbonate and quartz sand are added in sequence, the speed is increased to 1500 r / min and stirred and dispersed for 30 minutes, and the mixture is ground and dispersed using a sand mill for 1 hour, the speed is reduced to 300 r / min, and defoaming is carried out at a low speed for 30 minutes. The mixture is filtered through 100 mesh gauze and stirred evenly to obtain an epoxy resin composition; Step 2: According to the formula of the imitation stone self-leveling paint, the curing agent and the curing accelerator are mixed uniformly to obtain a curing agent composition; Step 3: adding the curing agent composition to the epoxy resin composition and stirring evenly to obtain a stone-like self-leveling paint; Among them, when the bifunctional rigid-flexible structured diluent is diluent X-Ⅰ, the prepared product is recorded as stone-like self-leveling paint Ⅰ; When the difunctional rigid-flexible structured diluent is diluent X-II, the prepared product is recorded as stone-like self-leveling paint II. Comparative Example 1:
[0022] A stone-like paint a was prepared, which differed from the stone-like self-leveling paint I only in that a conventional monofunctional epoxy reactive diluent (n-butyl glycidyl ether) was used to replace the bifunctional rigid-flexible structured diluent X-I. Comparative Example 2:
[0023] A stone-like paint b was prepared, which differed from the stone-like self-leveling paint I only in that a conventional difunctional aliphatic epoxy compound active diluent (1,4-butanediol diglycidyl ether) was used to replace the difunctional rigid-flexible structured diluent X-I. Comparative Example 3:
[0024] The stone-like paint C was prepared, which differed from the stone-like self-leveling paint I only in that the bifunctional rigid-flexible structured diluent X-I was not used. Performance testing:
[0025] 1. Leveling performance test of imitation stone self-leveling paint products: (1) Flowability test: Place the flowability test mold (a metal hollow cylinder with an inner diameter of 30 mm and a height of 50 mm) horizontally in the center of the glass test plate. The surface of the test plate should be flat and smooth without water droplets. Fill the flowability test mold with the sample and start timing. At 2 seconds, lift it vertically upward by 10 cm. Keep it at this height for 10 seconds to let the sample flow freely. After 4 minutes, record the diameters in two vertical directions and take the average of the two diameters. The diameter size is used to characterize its flowability. (2) Leveling grade test: Test the leveling grade of the sample according to JB / T 3998-1999 standard, and observe the appearance of the paint film after room temperature curing; The above performance test results are shown in Table 2; Table 2 Performance test results of imitation stone self-leveling paint
[0026] Use a 2mm trowel to apply the imitation stone self-leveling paint product on the surface of the calcium silicate board by trowel coating, and control the surface density at 1.0kg / m 2 After the room temperature curing is completed, a stone-like self-leveling paint film is formed, and the performance test is carried out. The results are shown in Table 3: Table 3 Performance test results of imitation stone self-leveling paint
[0027] By comprehensively analyzing the performance test results in Table 2 and Table 3, the following conclusions can be drawn: Conclusion 1: Referring to national industry standards and enterprise user requirements: when the fluidity is ≥140mm, the coating is considered to have self-leveling properties; Therefore, the imitation stone paint products prepared by the present invention meet the technical requirements of self-leveling properties specified in industry standards; Conclusion 2: The stone-like self-leveling paint product prepared using the independently developed bifunctional rigid-flexible structured diluent of the present invention has achieved significant improvements in mechanical properties (hardness and wear resistance), water resistance, and corrosion resistance compared to epoxy paints using conventional epoxy reactive diluents. Among them, the stone-like self-leveling paint II prepared using the bifunctional rigid-flexible structured diluent X-Ⅱ has better water resistance.
Claims
1. A stone-like self-leveling paint, characterized in that: The composition comprises the following raw materials in parts by weight: 45-55 parts of bisphenol A glycidyl ether type epoxy resin; 5-15 parts of a bifunctional rigid-flexible structured diluent; 10-15 parts filler; 5-15 parts aggregate; 15-20 parts of curing agent; 0.1-0.5 parts of curing accelerator; The bifunctional rigid-flexible structured diluent is prepared by firstly subjecting 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane or terminal chloromethyl hexasiloxane monomers, which provide a flexible structure, to a nucleophilic substitution reaction with 3-cyclohexene-1-methanol, which provides a rigid structure, and then epoxidizing the cyclohexene group.
2. A stone-like self-leveling paint according to claim 1, characterized in that: The bifunctional rigid-flexible structured diluent is bifunctional rigid-flexible structured diluent X-I or X-II; The chemical structural formula of the diluent X-Ⅰ is: ; The chemical structural formula of the diluent X-II is: 。 3. The stone-like self-leveling paint according to claim 1, characterized in that: The filler is one or a combination of kaolin, talc, calcium carbonate and barium sulfate.
4. The stone-like self-leveling paint according to claim 1, characterized in that: The aggregate is colored quartz sand or glass sand.
5. The preparation process of a stone-like self-leveling paint according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: According to the formula of the stone-like self-leveling paint, bisphenol A glycidyl ether epoxy resin and a bifunctional rigid-flexible structural diluent are first mixed, and then fillers and aggregates are added and stirred evenly to obtain an epoxy resin composition; Step 2: According to the formula of the imitation stone self-leveling paint, the curing agent and the curing accelerator are mixed uniformly to obtain a curing agent composition; Step 3: adding the curing agent composition to the epoxy resin composition and stirring evenly to obtain the stone-like self-leveling paint.
6. The preparation process of a stone-like self-leveling paint according to claim 5, characterized in that: The bifunctional rigid-flexible structured diluent is bifunctional rigid-flexible structured diluent X-I, and its preparation method is as follows: Under the action of a phase transfer catalyst, the chlorine functional group of 1 molar equivalent of 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane reacts with the hydroxyl functional group of 2.01-2.09 molar equivalents of 3-cyclohexene-1-methanol to produce a terminal cyclohexenyl disiloxane monomer; Under the oxidizing action of organic peroxyacid, the cyclohexene functional group in the terminal cyclohexenyl disiloxane monomer undergoes epoxidation reaction to generate a bifunctional rigid-flexible structured diluent X-Ⅰ.
7. The preparation process of a stone-like self-leveling paint according to claim 5, characterized in that: The bifunctional rigid-flexible structured diluent is bifunctional rigid-flexible structured diluent X-II, and its preparation method is as follows: Under the action of a phase transfer catalyst, the chlorine functional group of 1 molar equivalent of 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane reacts with the hydroxyl functional group of 2.01-2.09 molar equivalents of 3-butene-1-ol to produce a terminal alkenyl disiloxane monomer; Based on the silanol condensation reaction mechanism, a hydrogen-containing chloromethylsiloxane monomer is generated by a condensation reaction between the hydrolysis product of 1 molar equivalent of chloromethylethoxydimethylsilane and the hydrolysis product of 1.01-1.09 molar equivalents of dimethylethoxysilane; The terminal chloromethyl hexasiloxane monomer is generated by an addition reaction of the alkenyl functional group of 1 molar equivalent of the terminal alkenyl disiloxane monomer with the Si-H functional group of 2.01-2.09 molar equivalents of the hydrogen-containing chloromethylsiloxane monomer; Under the action of a phase transfer catalyst, a chlorine functional group of 1 molar equivalent of a terminal chloromethyl hexasiloxane monomer and a hydroxyl functional group of 2.01-2.09 molar equivalents of 3-cyclohexene-1-methanol undergo a nucleophilic substitution reaction to generate a terminal cyclohexenyl hexasiloxane monomer; Under the oxidizing action of organic peroxyacid, the cyclohexene functional group of the terminal cyclohexenyl hexasiloxane monomer undergoes epoxidation reaction to generate a bifunctional rigid-flexible structured diluent X-Ⅱ.
8. The preparation process of a stone-like self-leveling paint according to claim 6 or 7, characterized in that: The phase transfer catalyst is one of tetrabutylammonium bromide, tetrabutylammonium hydrogen sulfate and benzyltriethylammonium chloride.
9. The preparation process of a stone-like self-leveling paint according to claim 6 or 7, characterized in that: The organic peroxy acid is one of peracetic acid, perbenzoic acid and m-chloroperbenzoic acid.
10. Use of a stone-like self-leveling paint according to any one of claims 1 to 4, characterized in that: The stone-like self-leveling paint is used in scenarios where the ground surface requires wear resistance and corrosion resistance.
Citation Information
Patent Citations
Easy-to-release photosensitive resin for 3D printing and preparation method thereof
CN106832149A
Solvent-free color-sand self-leveling top finish and preparation method thereof
CN108948952A
Bio-based silicon-oxygen bond-containing epoxy resin and preparation method and application method thereof
CN113583216A
Organic silicon modified epoxy resin and application thereof as coating agent
CN116199860A
Epoxy reactive diluent and preparation method thereof
CN118221719A